Detection and separation of lycopene and beta-carotene in tomato products: a new and sustainable chromatographic approach - Dias, Alice (2017)
Science experiments are crucial tools in the teaching/learning process because students learn more effectively doing by themselves. In the chemical education, experiments revealing the chemistry around us through high visual impact activities are particularly motivating and may influence students to choose Chemistry for a future career. Plant pigments, due to their beautiful colours and their vital importance in life on Earth, are privileged molecules for establishing important relationships between chemistry and daily life in classroom.1 Carotenoids are the yellow-orange pigments occurring in flowers, fruits and leaves, where they play essential functions in photosynthesis and photo protection. They possess high antioxidant activity providing protection against aging and human diseases like, cancer, cardiovascular diseases.2 Moreover, some carotenoids, such as β-carotene, additionally have provitamin A activities which is essential for vision process. Carotenoids also contribute to the colours of some birds (flamingo, canary), insects, and marine animals (shrimp, lobster, and salmon). Animals and humans are incapable of carotenoid biosynthesis and they should be obtained from the diet. Lycopene is an unsaturated carotenoid with antioxidant properties superior to those of β-carotene, which finds important applications in the food, pharmaceutical and cosmetic industries.2 It gives the red colour to several commonly consumed fruits and vegetables, representing more than 80% of total tomato carotenoids. Besides lycopene, beta-carotene is also present in tomato. As an extension a previous work,2 we here report another high visual impact and eco-friendly experiment enabling the separation of beta-carotene and lycopene from tomato sources using sustainable chromatographic techniques. This activity may be implemented in basic and secondary schools, allowing the teaching/learning of several key concepts of the Chemistry Curricula listed for Basic and Secondary Education.